ANALISIS KUALITATIF DAN KUANTITATIF PENGGUNAAN ANTIBIOTIK PADA PASIEN PASCA OPERASI LAPAROTOMI DI RUANG ICU RSUD JENDERAL AHMAD YANI METRO LAMPUNG TAHUN 2023: ANALISIS KUALITATIF DAN KUANTITATIF PENGGUNAAN ANTIBIOTIK PADA PASIEN PASCA OPERASI LAPAROTOMI DI RUANG ICU RSUD JENDERAL AHMAD YANI METRO LAMPUNG TAHUN 2023 - Kurniati, Rizki; Sumiyati, Yati; Ramadaniati, Hesty Utami; Syahputri, Devina Harti (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Laparotomy is a surgery performed to open the abdomen, a form of major surgery by cutting the layers of the abdominal wall, risking causing infection of the surgical wound where antibiotics are given as treatment. Antibiotic resistance can lead to increased morbidity, mortality and health costs, therefore there needs to be an analysis for the use of antibiotics. The analysis of the use of antibiotics was carried out in the ICU room of the General Ahmad Yani Metro Lampung Hospital with the aim of analyzing how to use antibiotics qualitatively and quantitatively. The method used is descriptive with retrospective data collection from the period of January 1 to December 31, 2023. The qualitative analysis of the use of antibiotics used the Gyssens method and quantitatively with the ATC/DDD du 90% method. The sample of this study consisted of 52 patients after laparotomy surgery in the ICU room of General Ahmad Yani Metro Hospital Lampung, where based on the inclusion and exclusion criteria determined. Based on the results of the analysis of antibiotic use with the Gyssens method, 83.8% used antibiotics non-adherence (category 0) and 16.2% used antibiotics adherence (categories VIA and V). Analysis of the use of antibiotics using the ATC/DDD method obtained that Seftriaxone had the highest DDD with DDD/100 patients – 76.4 DDD per day and those in the DU segment of 90% were Seftriaxone and Metronidazole. Keywords: ATC/DDD du 90%, Gyssens, Laparotomy, Quantitative, Qualitative